Use of Contemporary Protease Inhibitors and Risk of Incident Chronic Kidney Disease in Persons With Human Immunodeficiency Virus: the Data Collection on Adverse Events of Anti-HIV Drugs (D:A:D) Study - Ryom, Lene; Dilling Lundgren, Jens; Reiss, Peter; Kirk, Ole; Law, Matthew; Ross, Mike; Morlat, Phillip; Andreas Fux, Christoph; Fontas, Eric; De Wit, Stephane; D'Arminio Monforte, Antonella; El-Sadr, Wafaa; et al. (The Journal of infectious diseases, 2019)
It is unclear whether use of contemporary protease inhibitors pose a similar risk of chronic kidney disease (CKD) as use of older protease inhibitors. Participants in the Data Collection on Adverse Events of Anti-HIV Drugs (D:A:D) study were followed up until the earliest occurrence of CKD, the last visit plus 6 months, or 1 February 2016. Adjusted Poisson regression was used to assess associations between CKD and the use of ritonavir-boosted atazanavir (ATV/r) or ritonavir-boosted darunavir (DRV/r). The incidence of CKD (10.0/1000 person-years of follow-up; 95% confidence interval, 9.5-10.4/1000 person-years of follow-up) increased gradually with increasing exposure to ATV/r, but the relation was less clear for DRV/r. After adjustment, only exposure to ATV/r (adjusted incidence rate ratio, 1.4; 95% confidence interval, 1.2-1.6), but not exposure to DRV/r (1.0; .8-1.3), remained significantly associated with CKD. While DRV/r use was not significantly associated with CKD an increasing incidence with longer ATV/r use was confirmed.